Assessment of Grassroots Empowerment Programs for Economic Development in Anambra State, Nigeria (Quest Journal of Management and Social Sciences, 2021)
Background: The work is anchored on community development theory and decentralization process which emphasize both a holistic approach to development and transfer of power, functions, competencies, and means from the central government to the regional and local governments at the grassroots.Objective: The study assessed the Anambra State Government’s Grassroots Development Scheme for economic empowerment of community dwellers, in all the local governments of Anambra state, in Southeastern Nigeria. This was with the view to determine the extent of involvement of all the communities in the Government’s Grassroots Development Scheme and the commitment of the people to the purpose for which the development scheme was initiated. Method: The primary source of data was used for the study. The population was made up of all the indigenes of Anambra State. The total number of respondents selected for the study is 975. Data collected were analyzed using descriptive and inferential statistics.Result: The result showed that all the communities were involved in the grassroots development scheme of the Government of Anambra state (χ2=698.211, df =4, p=0.00). The research findings also showed that the communities were committed to the purpose for which the grassroots scheme was initiated (r=0.747, p=0.00). Conclusion: The study, therefore, concludes that all the communities in Anambra State were included in the grassroots development scheme of Anambra State and that the people of Anambra State were committed to the scheme as they embarked on and completed different development projects in the state